Women and the university curriculum : towards equality, democracy, and peace - Kearney, Mary-Louise ; Rønning, Anne Holden (J. Kingsley Publishers, 2020)
Women, higher education and development / M.-L. Kearney -- The experience of feminine leadership in the academy / S.L. Bond -- The university curriculum, law and gender / H. Mensa-Bonsu -- Women and development / M.I. D'Avilo-Neto -- Women's health : a model of an integrated curriculum / K. Sherif and S.P. Levison -- Gender and the curriculum in commerce and management studies / M. Gardner and M. King -- Women's studies in Bulgarian universities / R. Muharska -- Science and technology in China / Z. Gui -- Gender in science and technology : the New Zealand experience / R. Dormer -- Public administration / M.T. Gallego and O. Mó -- Gender in demography and population studies at university level / M.L. Samman -- The gender dimension in agronomy : a student perspective / W. Tuinstra -- Peace studies / S.W. Osseiran -- Teacher training and the promotion of gender equality : a case study of Israeli society / R. Shachar